2007
DOI: 10.1111/j.1471-0528.2007.01289.x
|View full text |Cite|
|
Sign up to set email alerts
|

Cost‐effectiveness of antenatal screening for neonatal alloimmune thrombocytopenia

Abstract: Objectives To estimate the costs and health consequences of three different screening strategies for neonatal alloimmune thrombocytopenia (NAIT).Design Cost-utility analysis on the basis of a decision tree that incorporates the relevant strategies and outcomes.Setting Three health regions in Norway encompassing a 2.78 million population.Population Pregnant women (n = 100,448) screened for human platelet antigen (HPA) 1a and anti-HPA 1a antibodies, and their babies.Method Decision tree analysis. In three branch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 35 publications
1
45
0
1
Order By: Relevance
“…37 However, there are increased costs associated with elective CS compared with planned vaginal delivery and we have calculated the average costs per CS, including possible additional costs associated with treatment of neonates with pulmonary maladaption, to be approximately US $4800. 38 This calculation is part of a comprehensive cost-effectiveness analysis where we show that the screening and intervention program applied to a population of 100 000 pregnant women would save 210 to 230 qualityadjusted life years and, at the same time, reduce health care costs by approximately US $2.2 million. 38 An important weakness of the present study is the absence of a control group consisting of planned vaginal deliveries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 However, there are increased costs associated with elective CS compared with planned vaginal delivery and we have calculated the average costs per CS, including possible additional costs associated with treatment of neonates with pulmonary maladaption, to be approximately US $4800. 38 This calculation is part of a comprehensive cost-effectiveness analysis where we show that the screening and intervention program applied to a population of 100 000 pregnant women would save 210 to 230 qualityadjusted life years and, at the same time, reduce health care costs by approximately US $2.2 million. 38 An important weakness of the present study is the absence of a control group consisting of planned vaginal deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…38 This calculation is part of a comprehensive cost-effectiveness analysis where we show that the screening and intervention program applied to a population of 100 000 pregnant women would save 210 to 230 qualityadjusted life years and, at the same time, reduce health care costs by approximately US $2.2 million. 38 An important weakness of the present study is the absence of a control group consisting of planned vaginal deliveries. If we had conducted an RCT, the GPs should have been willing and able to explain to the pregnant women the implications of being included in the trial and the consequences of being randomized to one or the other study arm.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have published calculations of costs and potential benefits of screening and intervention, all coming to the same conclusion that such programs are likely cost-effective. [5][6][7][20][21][22] The main reason for cost-effectiveness, despite large-scale testing and, in the case of IVIG, expensive treatment, is the fact that the disease burden and costs for a child with lifelong severe neurologic damage from ICH is excessive.…”
Section: Perinatal Mortality and Neonatal Morbiditymentioning
confidence: 99%
“…Current research in the field is hopeful of a solution to these questions [11,21]. A large prospective screening and intervention study carried out in Norway from 1995 to 2004, including 154 HPA-1a-immunized women in 170 pregnancies, indicated that it is possible to reduce the risk for morbidity and mortality associated with FNAIT [3].…”
Section: Information Derived From Prospective Studiesmentioning
confidence: 99%
“…Other genetic and phenotypic markers are being studied to define the population more accurately. There are strong indications that a screening program would be clinically efficient [3], and also cost effective [21]. This evidence could be created as a result of a randomized study but this is considered unethical to perform.…”
Section: There Should Be a Defined Target Populationmentioning
confidence: 99%